Down-to-earth ecological literacy through human and nonhuman encounters in fieldwork. Issue 2 (4th March 2022) - Persson, Kristin; Andrée, Maria; Caiman, Cecilia
Abstract: This study explores how fieldwork can contribute to the development of ecological literacy and draws on actor-network theory and science studies which imply an understanding of agency as being distributed. The aim is to explore the consequences of the human-nonhuman encounters in fieldwork practice for the growth of ecological literacy. The explorations employ Bruno Latour's concept of "the terrestrial attractor" and its potential contributions to environmental education. The study is based on a field trip to experience black grouse lekking in Östergötland, Sweden. The empirical material consists of video- and audio-recordings. The results show two dimensions of encounters: (1) ways of initiating encounters, and (2) the human-learner actant configurations involved. The dimensions of encounters afford contributions to ecological literacy.